THE DUKE ELDER FAMILY/CAREGIVER TRAINING (DEFT) PROGRAM. (11th November 2018) - Hendrix, C; Matters, D; Griffin, T; Kramer, P; Batchelder, H; Prewitt, J; Park, H
Abstract: The decline in functional reserves and comorbidities complicate the recovery of older adults following a hospital discharge. Consequently, the assistance of family and friends (caregivers) while convalescing at home is particularly needed. The Duke Elder Family Caregiver Training (DEFT) Center offers a model for an academic-medical-community partnership for integrated caregiver support after hospital discharge. Thus, the goal of this presentation is to describe the conceptualization and structure of the DEFT and describe its preliminary results on caregiver preparedness and readiness for hospital discharge and patient readmission rates. The DEFT leverages the use of EPIC/Maestro for consult from hospital providers and designed its workflow to integrate its teaching as part of Duke's hospital discharge process. Graduate students from Duke School of Nursing participated in the DEFT caregiver program for course credits. Since 10 months of launching the DEFT caregiver training program, more than 200 consults were received from hospital providers in selected units for caregiver training. Of these, 76 were successfully approached and trained. Analyses of patient data revealed lower 30-day readmission rate of patients whose caregivers received DEFT training compared those who did not (5.9% vs 22%). Overall, an improvement in levels of caregiver preparedness and readiness for hospital discharge was observed within 14 days of training. Lessons learned from the initial launch of DEFT included allowing case managers to write consults for DEFT in addition to physicians and advanced practice providers; optimizing training location for caregiver convenience; and strategizing informational sessions about DEFT for hospital clinicians.